Usulan Perbaikan Layout Area Gudang Kering Logistik Menggunakan Metode Dedicated Storage di PT. Starfood International - Muhammad Syaiful Anam; Moch Nuruddin; Hidayat Hidayat (Jurnal Serambi Engineering, 2023)
PT. Starfoood International is a medium-sized industry engaged in fish processing which is used for snacks that have been exported to foreign countries. The company has a warehouse size of 20 meters wide x 50 meters long. Currently, the company is experiencing problems related to the arrangement of goods that are less organized and the company itself does not apply good layout procedures, which has an impact on the process of picking up goods which takes a relatively long time. The special storage method is a layout preparation method, in which the storage of products is arranged according to the number of import and export operations in the shortest distance. Through the use of this method, finished products that need to be stored will occupy the right place, making it easier for employees to store and remove products for production so that product flows smoothly. From the results of calculations using the dedicated storage method in the warehouse, the factors that influence 4 factors are Box (frozen fish), Box (Surimih), plastic (frozen fish), plastic (Surimih), for goods that are often in and out of the product manufacturing process at the factory placed behind the production door so that it doesn't take a long time and the items are arranged neatly, the calculation of the dedicated storage method is able to provide closer distance changes and make it easier for employees to find items that are often used.